Permanent Genetic Resources added to Molecular Ecology Resources Database 1 April 2013–31 May 2013. (12th August 2013) - ,; Agostini, Cecilia; Albaladejo, R. G.; Aparicio, A.; Arthofer, Wolfgang; Berrebi, P.; Boag, Peter T.; Carbone, Ignazio; Conroy, Gabriel C.; Cortesero, A. M.; Costa Gonçalves, Evonnildo; Costa, Diogo; et al.
Abstract This article documents the addition of 234 microsatellite marker loci to the Molecular Ecology Resources Database. Loci were developed for the following species: Acipenser sinensis, Aleochara bilineata, Aleochara bipustulata, Barbus meridionalis, Colossoma macropomum, Delia radicum, Drosophila nigrosparsa, Fontainea picrosperma, Helianthemum cinereum, Liomys pictus, Megabalanus azoricus, Pelteobagrus vachelli, Pleuragramma antarcticum, Podarcis hispanica type 1A, Sardinella brasiliensis and Sclerotinia homoeocarpa. These loci were cross‐tested on the following species: Acipenser dabryanus, Barbus balcanicus, Barbus barbus, Barbus cyclolepis, Drosophila hydei, Drosophila melanogaster, Drosophila obscura, Drosophila subobscura, Fontainea australis, Fontainea fugax, Fontainea oraria, Fontainea rostrata, Fontainea venosa, Podarcis bocagei, Podarcis carbonelli, Podarcis liolepis, Podarcis muralis and Podarcis vaucheri.